A REVIEW ON FUSION OF DIFFERENT DEFOGGING TECHNIQUES TO CLEAR IM IMPROVING PRIVATE EDUCATION SERVICE IN PUBLIC-PRIVATE PARTNERSHIP - Saidboev Shermirza Dodxomirzaevich; Yuldashev Kodirjon Mamadjanovich; Mamadaliev Axrorbek (International Engineering Journal For Research & Development, 2020)
In this article, the case of development of private educational institutions in the country and the ways of progress of the education service of marketing in these institutions were surveyed. Also, in the article, the development of state and non-state educational institutions of our country and foreign countries were leamt.